The Effectiveness of Peer Group Counseling Based on Pesantren in Increasing the Independence of Students in Islamic Boarding School Educational Institutions - Rakhmawati, Eni; Rani, Ariesza Puspita; Amaladni, Muhamad Ishlah (Universitas Pahlawan Tuanku Tambusai, 2025)
Independence is an important aspect in the development of students, especially in Islamic boarding schools that demand self-adjustment in a new environment. However, many students have difficulty adapting due to a lack of independence. This study uses a quantitative approach with a Quasi Experimental design of the Nonequivalent Control Group Design. The sample amounted to 18 students divided into the experimental group (n=9) and the control group (n=9). The research instruments are in the form of self-adjustment scales, sociometry, and counseling modules. Data were analyzed using the Mann-Whitney U test with the help of SPSS version 16.0. The average posttest score of the experimental group increased significantly from 51.18 to 67.86, while the control group only increased from 51.15 to 51.28. The Mann-Whitney test showed significant differences between the two groups (U=0.000; p0.05). These findings show that peer group counseling based on pesantren is effective in increasing student independence. This service is relevant to the cultural context of the pesantren because it involves peers as counselors, so that it is more in line with the needs of students. Peer group counseling has proven to be effective in increasing the independence of students at the Darqis Lebaksiu Islamic Boarding School.